2023
DOI: 10.26599/nre.2023.9120049
|View full text |Cite
|
Sign up to set email alerts
|

High sulfur loading and shuttle inhibition of advanced sulfur cathode enabled by graphene network skin and N, P, F-doped mesoporous carbon interfaces for ultra-stable lithium sulfur battery

Abstract: Achieving high loading of active sulfur yet rational regulating the shuttle effect of lithium polysulfide (LiPS) is of great significance in pursuit of high-performance lithium-sulfur (Li-S) battery. Herein, we develop a free-standing graphenenitrogen (N), phosphorus (P) and fluorine (F) co-doped mesoporous carbon-sulfur (G-NPFMC-S) film, which was used as a binder-free cathode in Li-S battery. The developed mesoporous carbon (MC) achieved a high specific surface area of 921 m 2 •g -1 with a uniform pore size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…The electrochemical impedance spectra (EIS) (Figure S45, Supporting Information) were obtained to show that the cells using Cu SA/N-Ti 3 C 2 T x /PP had the lowest interface impedance, which would be beneficial to ions/electrons transport. [10,73,74] Furthermore, the ability of Cu SA/N-Ti 3 C 2 T x to promote lithium ion transport was studied by variable CV curves at different scanning rates (Figure S46, Supporting Information). It could be seen that the cell with Cu SA/N-Ti 3 C 2 T x /PP showed enhanced D Li+ at peak 1 (3.7 × 10 −8 cm 2 s −1 ), peak 2 (5.2 × 10 −8 cm 2 s −1 ), and peak 3 (5.6 × 10 −8 cm 2 s −1 ), which meant that the single-atom coordination structure of Cu enhanced the transport of lithium ions.…”
Section: Electrocatalytic Performance Of Metal Single-atom Catalysts ...mentioning
confidence: 99%
“…The electrochemical impedance spectra (EIS) (Figure S45, Supporting Information) were obtained to show that the cells using Cu SA/N-Ti 3 C 2 T x /PP had the lowest interface impedance, which would be beneficial to ions/electrons transport. [10,73,74] Furthermore, the ability of Cu SA/N-Ti 3 C 2 T x to promote lithium ion transport was studied by variable CV curves at different scanning rates (Figure S46, Supporting Information). It could be seen that the cell with Cu SA/N-Ti 3 C 2 T x /PP showed enhanced D Li+ at peak 1 (3.7 × 10 −8 cm 2 s −1 ), peak 2 (5.2 × 10 −8 cm 2 s −1 ), and peak 3 (5.6 × 10 −8 cm 2 s −1 ), which meant that the single-atom coordination structure of Cu enhanced the transport of lithium ions.…”
Section: Electrocatalytic Performance Of Metal Single-atom Catalysts ...mentioning
confidence: 99%
“…Over the past few decades, many solutions have been used to deal with these encouraging limitations, and there have been great breakthroughs in the electrochemical performance of Li–S batteries. Initially, carbon materials were broadly used in Li–S batteries owing to their adjustable structure and good electrical conductivity. However, nonpolar carbon materials have very limited restrictions with LiPSs, which leads to severe capacity degradation especially under high sulfur loadings. For this, some polar materials have been employed as sulfur hosts in Li–S batteries for their strong chemisorption ability to LiPSs, such as metal oxides (Nb 2 O 5 and Fe 3 O 4 ), , sulfur oxides (Ce 2 O 2 S), metal sulfides (Co 9 S 8 , V 5 S 8 , and WS 2 ), ,, metal selenides (CoSe 2 and NiSe 2 ), , metal nitrides (TiN/TiC), and metal phosphides (FeP and NiCoP). , Typically, these metal compounds exhibit a very unique affinity to LiPSs by forming metal–sulfur bonds and have a remarkable effect in limiting the shuttle effect and accelerating the mutual conversion of LiPSs. , Moreover, defect engineering is essential to enhance the catalytic activity of these polar hosts for sulfur redox kinetics in both reversible discharge and charge processes of Li–S batteries. Particularly, introducing defects by anion or cation doping is significant for improving the electrocatalytic performance of the oxide catalysts. , For example, Wang and his colleagues reported that Fe-doped Co 3 O 4 microspheres showed abundant oxygen-rich defects, which provided much catalytic sites for LiPS capture and redox reactions …”
Section: Introductionmentioning
confidence: 99%
“…Doping heteroatoms into carbon materials can introduce extra pseudocapacitive active sites, which can signicantly improve the specic capacitance of carbon-based materials. [27][28][29][30][31] Conductive polymers or metal oxides can also be combined with high electrical conductivity carbon materials to achieve the purpose of complementary advantages. [32][33][34] The common methods such as the hydrothermal method, electrodeposition, co-precipitation and sol-gel method used in the preparation of heteroatom doped carbon and composite materials can improve the conductivity and increase the active sites to a certain extent.…”
Section: Introductionmentioning
confidence: 99%